Fouling bryozoans in Argentine harbours (Southwest Atlantic): new records and the description of a new species - López-Gappa, Juan; Liuzzi, María G.; Castro, Karen L.; Bobinac, Magalí; Schwindt, Evangelina (Zootaxa, 2022)
Non-indigenous bryozoans are frequent components of biofouling assemblages in harbour environments worldwide. We performed a survey of artificial hard substrates in six harbours spanning 16 degrees of latitude along the coast of Argentina, from Ingeniero White (38º47′ S) to Ushuaia (54º48′ S). Microeciella argentina n. sp., distributed in warm-temperate waters of northern Patagonia and Buenos Aires Province, is described. The non-indigenous species (NIS) Callopora dumerilii, Smittoidea spinigera and Stephanollona boreopacifica are recorded here for the first time in the Southwest Atlantic. Their occurrence in fouling assemblages of warm-temperate harbours and their previous absence in these areas suggest that they probably arrived in Argentina by international shipping traffic. Callopora dumerilii is native to Europe and the northeast Atlantic. Smittoidea spinigera and Stephanollona boreopacifica are native to China and Korea, respectively. The morphological differences between S. spinigera and the Californian species S. prolifera, which is invading European harbours in the North Sea, are discussed. Bugula neritina, Bugulina flabellata, Cryptosula pallasiana and Fenestrulina delicia, common in harbours of Buenos Aires Province, are here recorded in Patagonia, highlighting the importance of regional shipping traffic to secondary spread of NIS. Arachnidium fibrosum, Buskia socialis, Anguinella palmata, Aetea cultrata, Bicellariella edentata and Exochella moyanoi, previously known from Brazil, and Hippothoa divaricata, are here recorded in Argentina. This study shows that warm-temperate harbours in Buenos Aires Province and northern Patagonia are particularly prone to the introduction of non-indigenous bryozoans.